Implementing auralized CPB sounds on a pedestrian simulator - Soares, Francisco Emanuel Cunha (2021)
Recently, several studies on pedestrian safety and particularly those addressing pedestrian crossing behaviour and decision-making have been performed using virtual reality systems. The use of simulators to assess pedestrian behaviour is conditioned by the feeling of presence and immersion, for which the sound is a determining factor. This paper presents an implementation procedure in which tyre-road noise samples are auralized and presented as auditory stimuli in a virtual environment, for assessing pedestrian crossing decision-making. The auditory samples obtained through the Close Proximity (CPX) method and subsequently auralized to represent Controlled Pass-By (CPB) recordings reproduce the sounds of a vehicle approaching a crosswalk. The auralized sounds together with the presentation of visual stimuli were used in an experiment carried out with 15 participants. Safety indicators, such as the time-to-passage at the moment that participants decided to cross a virtual crosswalk and the minimum time-to-collision were registered and compared with data obtained in real-world road crossings. The comparison of the results obtained in virtual and real environments, indicated a good suitability of the approach for studying pedestrian crossing behaviour.